Continuous Team Assessment to Improve Student Engagement and Active Learning - Esposto, Alexis; Weaver, Debbi (Journal of University Teaching and Learning Practice, 2011)
A strategy of continuous team assessment over three years, comprising of a series of tests and a major project, was introduced into scheduled tutorial classes in an attempt to improve flagging attendance and low student motivation. The assessment tasks were designed to be undertaken in teams of two students, with ongoing feedback as an integral component. After a single semester of implementation, attendance at tutorials improved (to nearly double the previous year), and this rate was sustained over a three year period. Average assessment marks rose a full grade compared to the previous student cohort, and this was also sustained over the same period. Students’ output improved, and they were actively engaged in their work and with their colleagues. These results indicate the change in assessment strategy achieved the desired outcomes of improving student engagement and active learning.